Macroeconomics theories and policies - Froyen, Richard T. (Pearson Education Limited, 2013)
Macroeconomicstraces the history, evolution, and challenges of Keynesian economics, presenting a comprehensive, detailed, and unbiased view of modern macroeconomic theory